(untitled) (Nóema, 2020)
In 1919, Alfred North Whitehead participated in an interdisciplinary symposium on the ultimate data of science, showing how neither time nor space nor any kind of material can play this role. According to him, nature is instead a constantly growing whole of events and objects that intersect and overlap each other, totally irreducible to any materialistic and atomistic view. The text, previously unpublished in Italian, presents itself as an effective insight on some key-concepts of Whitehead’s philosophy (event, object, cogredience, creative advance) and is accompanied by a brief introduction, useful to contextualize it.